PENGARUH AUDIT DELAY, LEVERAGE, OPINI AUDIT TAHUN SEBELUMNYA DAN UKURAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN - Wahyuni, Nabillah Nur; Michael, Michael (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study was conducted with the aim of analyzing the factors that influence going concern audit opinion based on audit delay, leverage, previous year's audit opinion and company size. The sample of this study used energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period using purposive sampling techniques. The research method used is an associative quantitative approach with secondary data sources in the form of financial statements. This study uses SPSS version 26 to perform logistic regression analysis. This study found that leverage and the previous year's audit opinion affect going concern audit opinion. Meanwhile, audit delay and company size have no effect on going concern audit opinion